Aryl Hydrocarbon Receptor Modulation and Resveratrol Influence on Dnah1 Expression: Implications for Male Reproductive Health - Bustani, Ghadeer; Al-Humadi, Nabil; Alghetaa, Hasan (The Iraqi Journal of Veterinary Medicine, 2024)
Male reproductive health is intricately regulated by molecular and physiological processes, with the aryl hydrocarbon receptor (AhR) playing a crucial role. AhR is activated by various ligands and influences the onset and progression of diseases. The aim of this study was to evaluate the role of AhR on spermatogenesis in adult male rats were affected by resveratrol (RES) and CH223191, an AhR antagonist. The study include forty rats were randomly divided into four equal groups: Control group, DMSO group, RES group and AhR‾ group, the rats received respective treatments intraperitoneally twice weekly for 60 days, and various parameters related to male reproductive health were evaluated. The AhR that activation by the RES treatment were enhanced the sperm morphology, sperm acrosomal integrity and luteinizing hormone. Moreover, the Dnah1 gene expression, is has play major role in sperm morphology, was upregulated and testosterone levels were elevated by RES. On the other hand, sperm morphology, sperm acrosomal integrity, testosterone hormone levels, and Dnah1 expression were all reduced in AhR‍ rats. The testicular tissue integrity was maintained by RES, according to a histopathological analysis. These findings highlight the role of AhR in male reproductive health and suggest RES as a potential therapeutic agent.